2021
DOI: 10.1155/2021/5663302
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Hybrid Models for Weekly Stock Market Index Prediction: Empirical Evidence from SAARC Countries

Abstract: The foremost aim of this research was to forecast the performance of three stock market indices using the multilayer perceptron (MLP), recurrent neural network (RNN), and autoregressive integrated moving average (ARIMA) on historical data. Moreover, we compared the extrapolative abilities of a hybrid of ARIMA with MLP and RNN models, which are called ARIMA-MLP and ARIMA-RNN. Because of the complicated and noisy nature of financial data, we combine novel machine-learning techniques such as MLP and RNN with ARIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…e productive input variables, the set of neurons and layers within a hidden variable, and the optimal model framework are established automatically in the GDMH algorithm [37]. In our study, we select these parameters through error and trial approach, followed by Peng et al [38]. e mapping amid target and input variables is carried out via GMDH-NN, and a nonlinear function is so-called Volterra series, given in equation (30) as follows:…”
Section: Group Methods Of Data Handling (Gmdh)mentioning
confidence: 99%
“…e productive input variables, the set of neurons and layers within a hidden variable, and the optimal model framework are established automatically in the GDMH algorithm [37]. In our study, we select these parameters through error and trial approach, followed by Peng et al [38]. e mapping amid target and input variables is carried out via GMDH-NN, and a nonlinear function is so-called Volterra series, given in equation (30) as follows:…”
Section: Group Methods Of Data Handling (Gmdh)mentioning
confidence: 99%
“…Rezaei [15] extracted financial data depth features and established CEEMD-CNN-LSTM and EMD-CNN-LSTM hybrid algorithms, and the experimental results show that CEEMD has a better prediction effect compared to EMD. Zhang [16] combined MLP and RNN with ARIMA, respectively, to build ARIMA-MLP and ARIMA-RNN hybrid models, and validated them on three sets of stock data. The results all showed that the hybrid models have stronger robustness than the individual models.…”
Section: Decomposition Of Time Series Datamentioning
confidence: 99%
“…In reference [22], the Automatic ARIMA algorithm is discussed to forecast stock returns from 50 stocks of the Indian National Stock Exchange's minute-wise records. And in reference [23] the author recreates the ML model for stock market prediction to that of a weekly version of SAARC (India, Sri Lanka, Pakistan) countries using a hybrid model of ARIMA and RNN which decomposes the time-series into its linear and non-linear data components of stock prices. Additionally, research of fifty-six equities from seven sectors is done in the report [27].…”
Section: Applicationsmentioning
confidence: 99%